A Organoleptic Analysis of Tuna Meatballs (Thunnus sp.) with the Addition of Lindur Fruit Flour (Bruguiera gymnorrhiza) - Eny Heriyati; Andi Dela Afrilia; Muhammad Hirwan Wahyudi; Kaharuddin; Suprianto (Universitas Muhammadiyah Palembang, 2025)
This study aimed to analyze the effect and determine the best formulation of Lindur fruit flour (Bruguiera gymnorrhiza) as an alternative ingredient on the hedonic quality organoleptic characteristics (color, aroma, texture, and taste) of tuna fish balls (Thunnus sp.). The potential of natural resources in East Kutai as a coastal region, with its abundance of mangrove forests and high yield of tuna fish, is expected to support local food security and the diversification of processed tuna fish ball products through the addition of Lindur fruit flour. Lindur fruit, which is rich in fiber and bioactive compounds, has the potential to act as a binding agent and flavor enhancer for the diversification of tuna fish ball products. The treatments tested included the addition of Lindur fruit flour at concentrations of 20%, 40%, and 60% of the total flour content in the batter, compared to a control group (0% addition). The parameters tested were color, aroma, texture, and taste. The data were statistically analyzed using the General Linear Model: Univariate, followed by the Duncan test at a significance level of α = 0.05. The organoleptic test results indicated that the addition of Lindur fruit flour had a significant effect (P < 0.05) on all parameters tested. The formulation with 60% Lindur fruit flour addition was the most preferred by the panelists, achieving the highest scores for aroma and taste, and high acceptance scores for color and texture. Overall, the addition of Lindur fruit flour provided a more unique aroma profile and enhanced a savory taste that was appreciated by the panelists. It is concluded that the addition of Lindur fruit flour up to a 60% dosage effectively improved the organoleptic acceptance of tuna fish balls and successfully supported the diversification of processed tuna products. This finding recommends the 60% formulation for industrial application.